Caracterización de las pérdidas por infiltración con análisis estadístico de precipitación y escurrimiento. Issue 1 (1st January 2016) - Domínguez Mora, R.; Arganis-Juárez, M.L.; Carrizosa Elizondo, E.; Esquivel Gardu˜no, G.
Abstract: In this study runoff coefficients for different return periods from statistical analysis of rainfall and runoff and from the curve number method were obtained. For this purpose about 100 basins in different places of Mexico with more than 20 years of record in the hydrometric station were analyzed besides having few alterations by the construction of waterworks, without significant storage upstream of the hydrometric station, with an estimated time of concentration, less than 12 hours and with a ratio between the average of the annual maximum daily runoff and the average of the instantaneous maximum annual runoff lower than 0.5. It was found that runoff coefficients increase with increasing rainfall in the basin, but asymptotically tend to a limit value; the slope of the basin is a very important parameter which largely determines the runoff coefficients and the Curve number method overestimates the effective rainfall runoff and, therefore, the runoff coefficient. The overestimation tends to be higher as the rainfall in the basin increases.